How to Present Data in Tables and Figures in Health Research - Anconetani, María V.; Jancko Alavia, Irma L.; Carretero, Marcelina; Cirelli, Delfina; Posadas Martínez, María L. (Revista del Hospital Italiano de Buenos Aires, 2024)
The effective presentation of data in health research is achieved through strategically designed tablesand figures. These elements can capture readers’ attention and convey complex information visually.Tables organize intricate data concisely, with descriptive titles and layouts that facilitate comparison. Onthe other hand, figures must clearly state their communicative purpose. Both should be numbered andarranged in the text. They exhibit specific characteristics in terms of dissemination; for instance, postersrequire appropriate spacing and fonts for readability. In conclusion, tables and figures are valuable toolsfor summarizing and presenting information in health research.
Keywords: tables; figures; manuscript; posters; research report; data visualization